Determining factors in the homicide rate of the male population in Brazil: an empirical analysis based on panel data, by federation units in the period 1993-2014 (Research, Society and Development, 2021)
This article empirically assesses the determinants of homicide rates in the male population in Brazil. The study approaches the subject with panel data with fixed effect and random effect by Federation Units in the period 1993-2014. Using other explanatory variables, the impact of unemployment on the homicide rates of this population is discussed. Based on the two panel models, fixed effect and random effect, the results support the hypothesis that increases in the unemployment rate produce increases in homicide rates in the male population. The variables, degree of informality, percentage of income earned by people belonging to the poorest 50% group and expenditure on education and culture are also statistically significant in the study. In general, the worked variables confirmed the expected results.